2015
DOI: 10.1038/ncomms7711
|View full text |Cite
|
Sign up to set email alerts
|

Marine sequestration of carbon in bacterial metabolites

Abstract: Linking microbial metabolomics and carbon sequestration in the ocean via refractory organic molecules has been hampered by the chemical complexity of dissolved organic matter (DOM). Here, using bioassay experiments and ultra-high resolution metabolic profiling, we demonstrate that marine bacteria rapidly utilize simple organic molecules and produce exometabolites of remarkable molecular and structural diversity. Bacterial DOM is similar in chemical composition and structural complexity to naturally occurring D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
193
7
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(218 citation statements)
references
References 50 publications
(65 reference statements)
17
193
7
1
Order By: Relevance
“…One of the most promising techniques is, albeit its limitations, Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) 16 . The molecular diversity of microbially formed DOM assessed by this approach is very similar to natural oceanic RDOM 17,18 . A currently unresolved conundrum is the observation that RDOM is apparently produced by microorganisms from labile substrates with far higher efficiency than required to sustain the characteristics of the natural DOM pool 11,12,17 .…”
mentioning
confidence: 61%
“…One of the most promising techniques is, albeit its limitations, Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) 16 . The molecular diversity of microbially formed DOM assessed by this approach is very similar to natural oceanic RDOM 17,18 . A currently unresolved conundrum is the observation that RDOM is apparently produced by microorganisms from labile substrates with far higher efficiency than required to sustain the characteristics of the natural DOM pool 11,12,17 .…”
mentioning
confidence: 61%
“…However, with no terrestrial material in our culture experiments, the humic-like fluorescence has to be a direct product of autochthonous production and microbial transformation. Similar processes occurring in the open-ocean water column would explain the global observations of elevated fluorescence and correlations with AOU in the deep ocean (Chen and Bada, 1992;Yamashita et al, 2007;Yamashita and Tanoue, 2008;JĂžrgensen et al, 2011;CatalĂĄ et al, 2015) that has been linked to the remineralization of organic matter and formation of RDOM (Yamashita et al, 2007;Jiao et al, 2010;Hansell, 2013;Lechtenfeld et al, 2015).…”
Section: Spectral Properties Of Phytoplankton-derived Cdom and Bepommentioning
confidence: 94%
“…The structural complexity may arise as a direct result of marine snow formation and microbial processing. Aggregation during particle formation could bring aromatic aldehydes and ketones in close proximity with hydroxylated benzoic acid derivatives through the microbial reprocessing into more complex molecules such as RDOM (Lechtenfeld et al, 2015). The presence of these molecules in the same moiety could facilitate charge transfer interactions between electron acceptors and donors, which has been suggested for lignin derivatives (Del Vecchio and Blough, 2004;Baluha et al, 2013;Sharpless and Blough, 2014).…”
Section: Spectral Properties Of Phytoplankton-derived Cdom and Bepommentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing DOM degradation remains challenging, however, due to the complex nature of DOM, the variety of microbial metabolic pathways, and the various environmental conditions that regulate bacterial metabolism (Eichinger et al, 2011). Despite these challenges, much has been learned by tracking changes in DOC concentration and DOM composition during incubation experiments, including the variation in biomineralization rates as a function of DOM source (e.g., Moran and Zepp, 1997;Obernosterer and Benner, 2004), the relationship of microbial activity to the production of labile (e.g., Kawasaki and Benner, 2006) and refractory (e.g., Ogawa et al, 2001;Jiao et al, 2010;Lechtenfeld et al, 2015) DOM, and how bacterial-derived refractory material compares structurally to refractory DOM in the ocean (e.g., Osterholz et al, 2015). Studies using ultrahigh resolution mass spectrometry have revealed additional molecular-level transformations in DOM as a result of microorganism activity (Kujawinski et al, 2004), including a significant decrease in the molecular diversity of terrigenous DOM (Seidel et al, 2015) and a preferential degradation of oxygen-rich molecules on a time scale of several days (Kim et al, 2006;Medeiros et al, 2015c;Seidel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%